2020
DOI: 10.3390/ijerph17082958
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Stress Factors for Female Professors at Online Universities

Abstract: The aim of this paper is to analyze the primary stress factors female professors at online universities are exposed to. The technique used for the prospective and exploratory analysis was the Delphi method. Two rounds of consultations were done with fourteen judges with broad experience in health and safety at work and university teaching who reached a consensus of opinion regarding a list of nine psychosocial risk factors. Among the most important risk factors, mental overload, time pressure, the lack of a sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 50 publications
(55 reference statements)
0
50
0
9
Order By: Relevance
“…On the other hand, the proportion of techno anxiety (11.0%), which surpasses Techno fatigue (7.2%), tends to be coincident with the findings of Estrada et al [30] prior to COVID-19 pandemic and teleworking resulting from the quarantine of confinement, but the results of both manifestations have a higher distance, and the total level of technostresses is reduced in this sample greater than 6.8%. García-Gonzalez's study [51] also shows coincidences, although this research focuses on instrument validation, more than in technostress measuring and moderating variables comparison. It is important to consider that the vast majority of the teachers who answered the survey have formal education, which, according to Tarafdar et al [52], would be related to lower technostress levels.…”
Section: Discussionmentioning
confidence: 89%
“…On the other hand, the proportion of techno anxiety (11.0%), which surpasses Techno fatigue (7.2%), tends to be coincident with the findings of Estrada et al [30] prior to COVID-19 pandemic and teleworking resulting from the quarantine of confinement, but the results of both manifestations have a higher distance, and the total level of technostresses is reduced in this sample greater than 6.8%. García-Gonzalez's study [51] also shows coincidences, although this research focuses on instrument validation, more than in technostress measuring and moderating variables comparison. It is important to consider that the vast majority of the teachers who answered the survey have formal education, which, according to Tarafdar et al [52], would be related to lower technostress levels.…”
Section: Discussionmentioning
confidence: 89%
“…The most frequent actions implemented in this field have indirectly required teachers to adapt themselves to various changes in the occupational or social environment, namely to become more resilient and cope with stressors 11,12,24 . However, such an individualistic approach can ignore the sources of work stressors, such as aggression, lack of staff, and austerity measures, which are often beyond an individual's control 9,13,18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Teachers have become more exhausted and anxious because of the restrictions imposed by the pandemic, especially because of change of classical teaching methods into online/ remote teaching 7,18 . Moreover, many studies carried out during this tough period showed a greater vulnerability among female teachers in terms of experiences and consequences of burnout than men 14,19 . Previous studies have shown unfavorable changes in women in terms of exposing mental overload and work-family conflicts 9,19,20 .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…They had to change learning plans to adapt to the unique situation rapidly. Thus, the virtual classes were stressful for both teachers and students [18,[66][67][68][69].…”
Section: Mental Health In Ukrainian University Studentsmentioning
confidence: 99%